Ruby Lu, brave and true - Look, Lenore (Atheneum Books for Young Readers, 2004)
"Almost-eight-year-old" Ruby Lu spends time with her baby brother, goes to Chinese school, performs magic tricks and learns to drive, and has adventures with both old and new friends.